Determining Peanut Food Allergy among Allergic Patients in Basrah Governorate - Mahjar, Nasrien Thamer; Raisan, Shayma`a Jabbar (American Journal of Biology and Natural Sciences, 2025)
Background: Peanut allergy affects 1% - 4.5% of children. with the potential for severe reactions. Method: The current study was conducted on 90 human venous blood samples, which included 74 blood samples from allergic individuals and 16 samples were collected for healthy people as control samples, we Evaluation specific IgE for peanut antigen in all sera samples depending on ELISA assay. Also in this study were prepared antigen and Electrophoresis for protein Peanuts. Result: The results of the electrophoresis showed eight proteins in crud peanut antigens. the indirect ELISA test based on the IgE of peanut antigens in patients show that the females had the highest (29.73%) compared with males, also the fourth age group (49) recorded the highest rate (6.76%) compared to the other age groups, with a significant difference between them (p< 0.05). Conclusion: The current study concluded that the percentage of people at risk of food allergy to peanuts allergens was increased in Basrah province.